2016
DOI: 10.1159/000452220
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Factors and Stroke Incidence in Japanese Postmenopausal Women: The Ohasama Study

Abstract: Background: The association between stroke and menstrual factors, for example, age at the time of menarche and age at the time of menopause, has not been well studied so far and the findings are inconsistent. We sought to examine this association in Japanese postmenopausal women. Methods: We followed 1,412 postmenopausal women aged ≥35 without a history of stroke in Ohasama, Japan. Baseline data were collected using a self-administered questionnaire. Adjusted hazard ratios (HRs) and 95% CIs of each menstrual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
1
13
3
Order By: Relevance
“…An unexpected theme which emerged during the group discussions with young women was the mention of menstruation as a protective factor for stroke. This contradicts the findings from a study of 1,412 postmenopausal Japanese women ( Murakami et al ., 2016). The study showed that during the 12 year follow-up (1998–2010), menstrual factor such as early menarche was associated with incidence of stroke and cerebral infarction ( Murakami et al ., 2016).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…An unexpected theme which emerged during the group discussions with young women was the mention of menstruation as a protective factor for stroke. This contradicts the findings from a study of 1,412 postmenopausal Japanese women ( Murakami et al ., 2016). The study showed that during the 12 year follow-up (1998–2010), menstrual factor such as early menarche was associated with incidence of stroke and cerebral infarction ( Murakami et al ., 2016).…”
Section: Discussioncontrasting
confidence: 97%
“…This contradicts the findings from a study of 1,412 postmenopausal Japanese women ( Murakami et al ., 2016). The study showed that during the 12 year follow-up (1998–2010), menstrual factor such as early menarche was associated with incidence of stroke and cerebral infarction ( Murakami et al ., 2016). Since Murakami et al .…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Overall, two studies found that earlier menarche was associated with higher risk of stroke after adjustment for age at menopause 4,19 . Of these studies, Alonso de Lecinana et al found that the odds of stroke were 54% higher among women aged <12 years at menarche compared with those aged 13 years at menarche 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown an association between early AAM and earlier all-cause mortality, 5 cardiovascular mortality, 6 9 higher risk of breast cancer, 10 cardiovascular disease (CVD), 1 , 8 diabetes, 11 16 obesity 15 , 17 and metabolic syndrome. 15 , 18 21 Early AAM has also been associated with psychological disorders, depression, smoking and alcohol use in adolescence and early sexual behavior.…”
Section: Introductionmentioning
confidence: 99%